Trilogy of Philosophy of Science Thinking as a Stimulation of Collaboration Skills in Asian Community Education courses - Dewi Satria Ahmar; Muhammad Fath Azzajjad (Athena: Journal of Social, Culture and Society, 2025)
The Collaborative abilities are essential for student achievement in the educational environment of the twenty-first century. Nonetheless, both international and domestic evaluations have shown that college students frequently struggle to collaborate well with others, interact critically, and co-create knowledge. In order to foster collaborative abilities, this study intends to investigate the effects of incorporating the Trilogy of Scientific Philosophy Thinking ontology, epistemology, and axiology into the Asian Community Education course. The study used a posttest-only control group and a quasi-experimental design. Two courses were used: the control group got case studies with no philosophical integration, whereas the experimental group was instructed using case studies enhanced with philosophical trilogy materials. Purposive sampling was used to choose the sample, which included 60 college students. A collaborative skills questionnaire was used to gather data, and both descriptive and inferential statistics were used for analysis. According to the results, the experimental group outperformed the control group on all four aspects of collaboration: respect for variety, communication, accountability, and interdependence (p < 0.05). These findings demonstrate how philosophical reasoning might improve students' ability to work together in a meaningful way. Building future-ready students and transformational community educators requires introspective, ethical, and integrative thinking, all of which are fostered by incorporating philosophical frameworks into learning modules.